Pruritus: A Sensory Symptom Generated in Cutaneous Immuno-Neuronal Crosstalk - Szöllősi, Attila Gábor; Oláh, Attila; Lisztes, Erika; Griger, Zoltán; Tóth, Balázs István (Frontiers in Pharmacology, 2022)
Pruritus or itch generated in the skin is one of the most widespread symptoms associated with various dermatological and systemic (immunological) conditions. Although many details about the molecular mechanisms of the development of both acute and chronic itch were uncovered in the last two decades, our understanding is still incomplete and the clinical management of pruritic conditions is one of the biggest challenges in daily dermatological practice. Recent research revealed molecular interactions between pruriceptive sensory neurons and surrounding cutaneous cell types including keratinocytes, as well as resident and transient cells of innate and adaptive immunity. Especially in inflammatory conditions, these cutaneous cells can produce various mediators, which can contribute to the excitation of pruriceptive sensory fibers resulting in itch sensation. There also exists significant communication in the opposite direction: sensory neurons can release mediators that maintain an inflamed, pruritic tissue-environment. In this review, we summarize the current knowledge about the sensory transduction of pruritus detailing the local intercellular interactions that generate itch. We especially emphasize the role of various pruritic mediators in the bidirectional crosstalk between cutaneous non-neuronal cells and sensory fibers. We also list various dermatoses and immunological conditions associated with itch, and discuss the potential immune-neuronal interactions promoting the development of pruritus in the particular diseases. These data may unveil putative new targets for antipruritic pharmacological interventions.